Legal Certainty Of Oral Employment Agreements On Workers' Rights Carried Out By Termination Of Employment : Case Study Of Mamuju District Court Decision No. 2/PDT.SUS-PHI/2018/PN. Mam - Nur Hana Oktaviani; Muthia Sakti; Atik Winarti (International Journal of Law and Society, 2024)
Employment agreements are a crucial step in establishing the employer-employee relationship. While both the Indonesian Labor Law and the Job Creation Law encourage written agreements, verbal contracts are also legally recognized. Written employment agreements serve as a binding instrument and evidence, yet many labor relationships operate without them. This can lead to legal disputes, particularly regarding workers' rights, as exemplified in the Mamuju District Court Decision No. 2/PDT.SUS-PHI/2018/PN.Mam. This study employs a descriptive-analytical approach, adhering to the normative legal research method. Secondary data is gathered from primary legal materials, secondary legal materials, and tertiary legal materials. The findings reveal that workers' rights under verbal agreements are still protected by the Labor Law and the Job Creation Law. However, the absence of written documentation of agreed-upon terms for termination of employment can pose challenges in proving these terms in court. In the Mamuju District Court Decision No. 2/PDT.SUS-PHI/2018/PN, the court ordered the defendant to pay double the plaintiff's entitlements due to the wrongful termination of employment through coercion. The court found that the plaintiff's termination was unrelated to any company policy violation and could not be substantiated due to the lack of written documentation.